2020
DOI: 10.1093/ageing/afaa217
|View full text |Cite
|
Sign up to set email alerts
|

Choking as a cause of negative pressure pulmonary oedema (NPPE) in an older adult

Abstract: An 86-year-old female presented to the Emergency Department (ED) in respiratory distress after choking on a sandwich at home. Her family had noticed that she had had difficulty during and coughing after swallowing for several months. Her initial chest x-ray showed diffuse alveolar infiltrates in both lungs and blood tests showed normal white cells and C-Reactive Protein (CRP). She was started on intravenous antibiotics for presumed aspiration pneumonia and received 15 L of oxygen. However, the infiltration had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…PE is defined as fluid accumulation in the interstitial or alveolar space of the lung and is classified into two categories depending on the underlying causes: cardiogenic (CPE) and non-cardiogenic PE (NCPE) (Bouyssou et al, 2017;Glaus et al, 2010). NPPE is a well-known type of NCPE caused by upper airway obstruction such as chock, strangulation, tumors, or laryngospasms in humans (Bhattacharya et al, 2016;Lonergan et al, 2021;Herrick et al, 1990). Nevertheless, it could be a life-threatening emergency, and early diagnosis followed by rapid treatment of NPPE is still challenging because of the clinical similarities with other types of PE (Perina, 2003;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PE is defined as fluid accumulation in the interstitial or alveolar space of the lung and is classified into two categories depending on the underlying causes: cardiogenic (CPE) and non-cardiogenic PE (NCPE) (Bouyssou et al, 2017;Glaus et al, 2010). NPPE is a well-known type of NCPE caused by upper airway obstruction such as chock, strangulation, tumors, or laryngospasms in humans (Bhattacharya et al, 2016;Lonergan et al, 2021;Herrick et al, 1990). Nevertheless, it could be a life-threatening emergency, and early diagnosis followed by rapid treatment of NPPE is still challenging because of the clinical similarities with other types of PE (Perina, 2003;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the survival-to-discharge rate for respiratory distress treated with PPV was 62.5% in 16 dogs, although the cause of respiratory distress was congestive heart failure (Edwards et al, 2014). Human patients who have upper airway obstruction attempt to inspire against the obstruction (Herrick et al, 1990;Lonergan et al, 2021). This effort generates very low intrathoracic pressure, which results in increased venous return from systemic circulation and preload that causes PE (Herrick et al, 1990;Bhattacharya et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…NPPE by choking does not occur without markedly negative intrathoracic pressure and is, therefore, more common in younger patients. However, there is a report of NPPE after upper airway obstruction caused by a sandwich in an older patient [ 5 ]. In our case, it was caused by shiitake mushrooms, a food item that is similar to a lid blocking the airway, and it is believed that this food item suddenly came in contact with the airway and blocked it completely, resulting in the development of NPPE.…”
Section: Discussionmentioning
confidence: 99%
“…NPPE is caused by excessive negative pleural pressure due to inspiratory effort during upper airway obstruction. The most common cause of NPPE is laryngeal spasm after extubation ( 2 , 3 ), epilepsy, and choking due to aspiration ( 4 , 12 , 13 ), but few cases of NPPE caused by sleep apnea have been reported.…”
Section: Discussionmentioning
confidence: 99%